The Correlation between Anti-Smoking Campaign Exposure and Significant Others Communication Intensity with the Attitude to Quit Smoking - Endah Febrianti; Dra. Sri Widowati Herieningsih, MS (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
This research is based on the high number of smokers in Indonesia. Despite the efforts made by the government and all parties concerned with these issues, the number of smokers in Indonesia is still increasing every year. This research aims to determine the correlation between anti-smoking campaign exposure and significant others communication intensity with the attitude to quit smoking. The theories that are used to explain the correlation in this research are the protection motivation theory and the concept of significant others. This research used a non-probability sampling with purposive sampling type, with 50 respondents. The results of Pearson correlation analysis using SPSS show that between anti-smoking campaign exposure with the attitude to quit smoking has a positive correlation. It is seen from the significant value of 0.000 or less than 0.01 and a correlation value of 0.480 which indicates a significant correlation between the two variables. While the significant others communication intensity with the attitude to quit smoking also has a positive correlation. It is seen from the significant value of 0.000 or less than 0.01, and the correlation value of 0.785, indicating a strong correlation between these two variables. Related to these results, then the government and all parties concerned with smoking problem in Indonesia are suggested to further enhance the activities related to anti-smoking campaign, for example by extending public service announcements about the dangers of smoking in the media, particularly in television as it is the most frequently accessed media by the public.